2015
DOI: 10.3310/hta19400
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre randomised controlled trial and economic evaluation of continuous positive airway pressure for the treatment of obstructive sleep apnoea syndrome in older people: PREDICT

Abstract: BackgroundThe therapeutic and economic benefits of continuous positive airway pressure (CPAP) for the treatment of obstructive sleep apnoea syndrome (OSAS) have been established in middle-aged people. In older people there is a lack of evidence.ObjectiveTo determine the clinical efficacy of CPAP in older people with OSAS and to establish its cost-effectiveness.DesignA randomised, parallel, investigator-blinded multicentre trial with within-trial and model-based cost-effectiveness analysis.MethodsTwo hundred an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 177 publications
2
25
0
4
Order By: Relevance
“…There have been a few prospective cohort studies in which outcomes of symptoms of sleep apnea patients were observed after CPAP treatment. Similar to our results, in these studies, improvement in sleep quality, cognitive functions, and quality of life were observed [28,29]. It was observed both in our study and previous studies that people who use PAP treatment regularly have perfect outcomes [30,31].…”
Section: Discussionsupporting
confidence: 92%
“…There have been a few prospective cohort studies in which outcomes of symptoms of sleep apnea patients were observed after CPAP treatment. Similar to our results, in these studies, improvement in sleep quality, cognitive functions, and quality of life were observed [28,29]. It was observed both in our study and previous studies that people who use PAP treatment regularly have perfect outcomes [30,31].…”
Section: Discussionsupporting
confidence: 92%
“…Further comparison showed that CVD events were statistically decreased after CPAP treatment. However, only small changes in the total cholesterol and no improvement in blood pressure were detected in the McMillan and colleagues study [31]. Although CVD events are the first predictors of death for these elderly OSA people, Ou and his colleagues also pointed out that diabetes might be an independent risk factor for them [25].…”
Section: Discussionmentioning
confidence: 95%
“…used EQ-5Q in the McMillan study; CPAP was shown to improve quality of life both generic and disease specific [31]. To date, only one RCT assessed whether CPAP treatment improved pain tolerance in elderly patients with OSA.…”
Section: Revuesmentioning
confidence: 99%
“…Big data approaches are now being applied to sleep medicine by using huge sample size to answer important questions . By identifying patients at risk of developing OSA, preventative strategies could be used in high‐risk patients before complications develop or prior to the occurrence of irreversible changes, for example apoptosis in the hippocampus and age‐related changes …”
Section: New Diagnosticsmentioning
confidence: 99%